Expression of succinate dehydrogenase flavoprotein subunit in saccharomyces cerevisiae studied by lacZ reporter strategy. Effect of FLX1 deletion. - Giancaspero, T; Brizio, C; Wait, R; Boles, E; Barile, M (2007)
We described here the construction of two novel Saccharomyces cerevisiae strains in which the regulatory region of the SDH1 gene, coding for the succinate dehydrogenase flavoprotein subunit, was fused in frame to the reporter gene lacZ of E. coli, coding for beta-galactosidase. By this approach, SDH1 expression was studied in the yeast strain, flx1 delta-lacZ, lacking of a functional mitochondrial FAD translocator, Flx1p. The experiments described here are in line with the hypotesys that a correlation exists between defects in flavin cofactor homeostasis and mitochondrial apo-flavoprotein expression.